Reduction of Nickeliferous Laterite Ores by Liquefied Petroleum Gas (LPG) - B. ITAO, GEVELYN; M. ANACLETO, NATHANIEL (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Laterite ores, in which the nickel occurs in oxide form, represent a significant potential resource of metallic nickel. Since nickel·containing sulfide ores has high environmental effects due to acid waste disposal, it is necessary to develop new processing techniques of laterite ores. In the present research, reduction of Palawan limonitic laterite ore ((F,Ni)O(OH).nH20) using lhqufiedpetroleum gas (LPG) as reductant was investigated in a fixed bed laboratory reactor. Advantages in utilizing LPG as a reductant in recovering nickel from laterite ores by pyrometallurgical operation are as follows: allows as to operate at a lower temperature, and minimizes the cost of electrical energy and environmental concerns associated with production of metallurgical coke and pelletised ores. Pirstly, since the ore contains considerable moisture, both free and combined, it was calcined at 800°C for 2 hours prior to crushing and sizing. The reduction experiments were carried out in a temperature range of 500°C to 700°C and reaction times from 10 to 60 min. Phases of raw materials and reduced samples were analyzed by XRD The percent nickel reduced was highest at particle size of 150 um. The reduction rate of laterite ore increased with increasing temperature. Nickel and iron oxides in the ore were reduced to metallic nickel and iron at 700°C. No metallic carbide was formed due to the propane/butane cracking and rarbon deposition.